2018
DOI: 10.1002/pssb.201800245
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transfer at the Interface Between MnPc and F6TCNNQ

Abstract: Photoelectron spectroscopy in the core level as well as the valence band region has been used to determine the electronic properties of interfaces between manganese phthalocyanine (MnPc) and the strong electron acceptor F 6 TCNNQ. It is shown that charge transfer occurs at this interface which results in the oxidation (reduction) of MnPc (F 6 TCNNQ) at the interface. Our data indicate a full electron transfer with no evidence for hybrid states. The valence band data suggest that the interface remains insulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 55 publications
3
15
0
Order By: Relevance
“…For smaller coverages, a second species at 397.8 eV arises due to a larger contribution of the F 6 TCNNQ anion spectrum to the overall signal until for ML coverage only charged molecules are detected. A full ionization charge transfer can be considered for this substrate, which is also reported for F 4 TCNQ on gold 4 or F 6 TCNNQ on an organic donor film 8,17 . For a thickness of 0.7 nm, a fitted spectrum is plotted in Figure 3.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…For smaller coverages, a second species at 397.8 eV arises due to a larger contribution of the F 6 TCNNQ anion spectrum to the overall signal until for ML coverage only charged molecules are detected. A full ionization charge transfer can be considered for this substrate, which is also reported for F 4 TCNQ on gold 4 or F 6 TCNNQ on an organic donor film 8,17 . For a thickness of 0.7 nm, a fitted spectrum is plotted in Figure 3.…”
Section: Resultsmentioning
confidence: 90%
“…A full ionization charge transfer can be considered for this substrate, which is also reported for F 4 TCNQ on gold 4 or F 6 TCNNQ on an organic donor film. 8,17 For a thickness of 0.7 nm, a fitted spectrum is plotted in Figure 3. The 1.0 nm N1s spectrum cannot be fitted by two components only.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experiments have shown that ground-state integer-charge transfer occurs for ZnPc:F-TCNNQ 8,12 , leading to at least partial polaron pair formation on the host H H and dopant D D. As the absorption coefficients of these sub-gap states are typically very low 17 , we perform photothermal deflection spectroscopy (PDS) measurements at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…However, as reported for the well-studied case of zinc-phthalocyanine (ZnPc) and molecular p-dopant F-TCNNQ 811 , this understanding of the doping mechanism is incomplete. Judging from the energy levels of the isolated molecules 1,12,13 , the doping process is expected to be more efficient than is experimentally observed 8 .…”
Section: Introductionmentioning
confidence: 96%